2002
DOI: 10.1590/s0066-782x2002001200008
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic Abnormalities and Antiphospholipid Antibodies in Patients with Systemic Lupus Erythematosus

Abstract: Objective -Lupus anticoagulant and anticardiolipin antibodies (aCL)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 43 publications
1
10
1
Order By: Relevance
“…Anti-cardiolipin antibodies 84,85 were associated with PAH in several series of patients with SLE, similar to the findings in some studies of CTEPH. 86,87 In the study of Asherson et al, 85 68% of the patients with SLE and PAH had antiphospholipid antibodies.…”
Section: Evaluating Connective Tissue Disease or Other Risk Factors Fsupporting
confidence: 87%
“…Anti-cardiolipin antibodies 84,85 were associated with PAH in several series of patients with SLE, similar to the findings in some studies of CTEPH. 86,87 In the study of Asherson et al, 85 68% of the patients with SLE and PAH had antiphospholipid antibodies.…”
Section: Evaluating Connective Tissue Disease or Other Risk Factors Fsupporting
confidence: 87%
“…Previous studies have shown the prevalence of heart valve disease in SLE has ranged from 12 to 73% [16][17][18][19][20][21]. Vivero [22], while the prevalence of this report was higher than that of our study (15.6%).…”
Section: Discussioncontrasting
confidence: 84%
“…[32][33][34] Other studies have attributed LV hypertrophy in SLE to the additional presence of hypertension. [35][36][37][38] Our study documents that hypertension is not the primary cause of LV hypertrophy in SLE on the basis of comparable prevalences of hypertension in the patient and reference groups and on subgroup analyses in normotensive and hypertensive subjects demonstrating that the presence of both SLE and hypertension leads to increases in LV mass beyond the presence of hypertension alone. These findings are even more striking in that the diagnosis of hypertension may be less robust in SLE patients (ie, blood pressure may be primarily or exclusively elevated during flares, and antihypertensive medications were not discontinued for study purposes in SLE patients, whereas they were discontinued for weeks to months in our hypertensive referent subjects).…”
Section: Discussionmentioning
confidence: 60%